The relationship between physical activity, fatigue, sleep quality, and anxiety levels of students during the university examination period - Emine Baran; Ayşenur Yılmaz (Northwestern Medical Journal)
Aim: The aim of this study was to assess the physical activity level of university students during exam week and to investigate the relationship between physical activity level and the severity of fatigue, sleep quality, and anxiety.